LEGALITAS PENGGUNAAN BUKTI ELEKTRONIK DALAM HUKUM ACARA PERDATA - Qasthary, Auzan; Muttaqien, Al; Saputra, T. Yasman (Jurnal Sosial Humaniora Sigli, 2023)
ABSTRACTIn the increasingly advanced digital era, the development of information technology has changed various aspects of life, including the legal system. The use of electronic evidence in legal proceedings has become commonplace, especially in the context of civil procedural law. Electronic evidence such as electronic documents, e-mails, text messages, audio recordings, and video recordings has become an integral part of many legal cases. This study aims to examine the legality of using electronic evidence in civil procedural law. In today's digital era, the use of electronic technology in legal proceedings has become a common phenomenon. However, there is still debate about the legality and strength of electronic evidence in the context of civil procedural law. This study uses a normative legal research method by examining laws and regulations related to the use of electronic evidence in civil procedural law. The results of this study indicate that, although there are challenges to the use of electronic evidence, its legality has been recognized and regulated in laws and regulations. Thus, the use of electronic evidence can be an efficient and effective alternative to meeting the evidentiary needs in civil procedural law.Keywords : Legality, Electronic Evidence, Civil Procedure Code ABSTRAKDalam era digital yang semakin maju, perkembangan teknologi informasi telah mengubah berbagai aspek kehidupan, termasuk dalam sistem hukum. Penggunaan bukti elektronik dalam proses hukum telah menjadi hal yang umum, terutama dalam konteks hukum acara perdata. Bukti elektronik seperti dokumen elektronik, email, pesan teks, rekaman suara, dan rekaman video telah menjadi bagian integral dari banyak kasus hukum. Penelitian ini bertujuan untuk mengkaji legalitas penggunaan bukti elektronik dalam hukum acara perdata. Dalam era digital saat ini, penggunaan teknologi elektronik dalam proses hukum telah menjadi fenomena yang umum. Akan tetapi, masih terdapat perdebatan mengenai legalitas dan kekuatan bukti elektronik dalam konteks hukum acara perdata. Penelitian ini menggunakan metode penelitian hukum normatif dengan mengkaji peraturan perundang-undangan yang terkait dengan penggunaan bukti elektronik dalam hukum acara perdata. Hasil penelitian ini menunjukkan bahwa meskipun terdapat tantangan dalam penggunaan bukti elektronik, legalitasnya telah diakui dan diatur dalam peraturan perundang-undangan. Sehingga, penggunaan bukti elektronik dapat menjadi alternatif yang efisien dan efektif dalam memenuhi kebutuhan pembuktian dalam hukum acara perdata.Kata kunci: Legalitas, Bukti Elektronik, Hukum Acara Perdata